Implementation of the Green Dentistry Concept for Dentistry Practitioners - Pindobilowo, Pindobilowo; Ariani, Dwi; Karamoy, Youla (PT FORMOSA CENDEKIA GLOBAL, 2024)
The environment is a unit of space with all objects, forces, conditions, and living things including humans and their behavior. In Indonesia, according to the Ministry of Environment and Forestry, the volume of medical waste from 2,813 hospitals in Indonesia reaches 242 tons per day. Green Dentistry is a term in the field of oral health, with a new concept that combines dental practice with environmental preservation, which is based on the 4R principles of Rethink, Reduce, Reuse, and Recycle. Methodology using the Narrative Review method based on journal databases including: Pubmed, Google Scholar, and BMC Oral Health, where the authors used references from the last 10 years. Conclusion: Green Dentistry is needed by optimally utilizing materials and energy and still paying attention to environmental safety.